Refractory LCH With Secondary Intracranial PNET: A Case Report and Review of Literature. Issue 2 (March 2018) - Chayapathi, Varsha; Mahajan, Amita; Kalra, Manas
Abstract : The occurrence of second malignant neoplasms in patients with Langerhans cell histiocytosis is infrequent but has been reported. Here we report the case of a child with refractory Langerhans cell histiocytosis who was treated with cladribine and later developed a secondary intracranial primitive neuroectodermal tumor. The possible association of cladribine with second neoplasm is further discussed.